Choline PET and PET/CT in Primary Diagnosis and Staging of Prostate Cancer - S. Schwarzenböck, M. Souvatzoglou, B. J. Krause (Theranostics, 2012)
PET and PET/CT using [11C]- and [18F]-labelled choline derivates is increasingly being used for imaging of primary and recurrent prostate cancer. While PET and PET/CT with [11C]- and [18F]-labelled choline derivates in patients suffering from biochemical recurrence of prostate cancer has been examined in many studies that demonstrate an increasing importance, its role in the primary staging of prostate cancer is still a matter of debate. Morphological and functional imaging techniques such as CT, MRI and TRUS have demonstrated only limited accuracy for the diagnosis of primary prostate cancer. Molecular imaging with PET and PET/CT could potentially increase accuracy to localize primary prostate cancer. A considerable number of studies have examined the value of PET/CT with [11C]- and [18F]- labelled choline derivates for the diagnosis of primary prostate cancer with mixed results. Primary prostate cancer can only be detected with moderate sensitivity using [11C]- and [18F]choline PET and PET/CT. The detection rate depends on the tumour configuration. Detection is also limited by a considerable number of microcarcinomas that cannot be detected due to partial volume effects. Therefore small and in part rind-like tumours can often not be visualized. Furthermore, the differentiation between benign changes like prostatitis, high-grade intraepithelial neoplasia (HGPIN) or prostatic hyperplasia is not always possible. Therefore, at the present time, the routine use of PET/CT with [11C]- and [18F]-labelled choline derivates cannot be recommended as a first-line screening procedure for primary prostate cancer in men at risk. A potential application of choline PET and PET/CT may be to increase the detection rate of clinically suspected prostate cancer with multiple negative prostate biopsies, for example in preparation of a focused re-biopsy and may play a role in patient stratification with respect to primary surgery and radiation therapy in the future.